Renal outcomes of STOP-IgAN trial patients in relation to baseline histology (MEST-C scores) - Schimpf, Judith Isabel; Klein, Till; Fitzner, Christina; Eitner, Frank; Porubský, Štefan; Hilgers, Ralf-Dieter; Flöge, Jürgen; Groene, Hermann-Josef; Rauen, Thomas (BMC nephrology, 2018)
The Oxford classification of IgA nephropathy (IgAN) defines histologic criteria (MEST-C) that provide prognostic information based on the kidney biopsy. There are few data on the predictive impact of this classification in randomized clinical trial settings.
Gesehen am 12.03.2020